2013
DOI: 10.1002/mrm.25019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the MR compatibility of dental retainer wires at 7 Tesla

Abstract: ii Thesis abstractThe radio frequent (RF) safety of dental retainer wires at 7 tesla has been investigated. Previous studies on metal implant wires at lower field strengths indicate possible SAR increase and directly related a temperature rise of the tissue around the wire. In the Netherlands up to 40% of the younger adults have such a dental retainer wire, which at the moment is listed as a contraindication for 7 T head scans.The radio frequent (RF) field transmitted by the MR excitation head coil is responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Even in the younger population some implants are highly prevalent, for example dental retainer wires (local experience showed that approximately 25-50 % of the potential volunteers in this age range have such a retainer wire in place). Both simulations as well as phantom experiments of these wires showed that the maximum temperature rise is less than 1.6°C even when using five times the allowed SAR level [57]. No adverse effects have been observed after more than 20 volunteers with dental retainer wires have undergone head 7 T scans.…”
Section: Safety Of Implantsmentioning
confidence: 90%
“…Even in the younger population some implants are highly prevalent, for example dental retainer wires (local experience showed that approximately 25-50 % of the potential volunteers in this age range have such a retainer wire in place). Both simulations as well as phantom experiments of these wires showed that the maximum temperature rise is less than 1.6°C even when using five times the allowed SAR level [57]. No adverse effects have been observed after more than 20 volunteers with dental retainer wires have undergone head 7 T scans.…”
Section: Safety Of Implantsmentioning
confidence: 90%
“…Nevertheless, for future studies, this might be less of an issue, as recent literature confirms that not all metallic implants should be considered as a major contraindication for 7.0 T MRI. 18 Second, the current study is performed in a non-consecutive small group of patients with a symptomatic, high-grade stenosis. To validate the clinical benefit of visualizing CMIs more extensive research is warranted with asymptomatic patients, patients with a lower stenosis grade and healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…UHF sites tend to be cautious with respect to the higher resonance frequency, the various transmit radiofrequency (RF) coils, and the fact that 7T MRI currently is not medically indicated. Nevertheless, some UHF sites already have performed dedicated safety tests for passive implants (25)(26)(27)(28)(29)(30)(31)(32)(33) or have included carefully selected subjects with implants (34,35). Because manufacturers only have verified MRI of patients with implanted aneurysm clips to be conditional for some clips in an MR environment up to 3T, a detailed compliance test for 7T is a prerequisite before any examination.…”
Section: Introductionmentioning
confidence: 99%